Coupling land-use change and hydrologic models for quantification of catchment ecosystem services - Yalew, S.G.; Pilz, T.; Schweitzer, C.; Liersch, S.; Kwast, J. van der; Griensven, Ann van; Mul, Marloes L.; Dickens, Chris; Zaag, P. van der (Elsevier, 2018)
Representation of land-use and hydrologic interactions in respective models has traditionally been problematic. The use of static land-use in most hydrologic models or that of the use of simple hydrologic proxies in land-use change models call for more integrated approaches. The objective of this study is to assess whether dynamic feedback between land-use change and hydrology can (1) improve model performances, and/or (2) produce a more realistic quantification of ecosystem services. To test this, we coupled a land-use change model and a hydrologic mode. First, the land-use change and the hydrologic models were separately developed and calibrated. Then, the two models were dynamically coupled to exchange data at yearly time-steps. The approach is applied to a catchment in South Africa. Performance of coupled models when compared to the uncoupled models were marginal, but the coupled models excelled at the quantification of catchment ecosystem services more robustly.